Assessment of HIV Prevalence and Sexual Behaviours Among Men Who Have Sex with Men in Cyprus, 2011–2012 - Pylli, Magdalini; Raftopoulos, Vasilios; Middleton, Nicos; Charalambous, Andreas; Paraskeva, Dimitra (My University, 2013)
Background : Men who have sex with men (MSM) comprise the most vulnerable group for HIV infection. Aim of this study was the estimation (1) of HIV prevalence and (2) sexual behaviours among MSM in Cyprus. Sample and Methods time location sampling has been used to recruit a representative sample of MSM in Cyprus during January 2011 to January 2012. Self completed questionnaires and Orasure oral fluid collection kits were distributed to men who were frequented in gay venues. Ethical approval was obtained by the Cyprus National Bioethics Committee.Results 200 MSM participated in the study. The response rate was quite high (89%). HIV prevalence was 2.5%. The mean age was 29 ± 6.6 years old while 74.9% of MSM identified themselves as gay. The prevalence of last unprotected anal intercourse was 30% while the last unprotected oral sex was 87.7%. The percentage of the participants who reported they have used alcohol and cocaine before or during the last sexual contact were around 60% and 10% respectively. One out of three has not been tested for HIV the last 12 months neither they know where they can get tested for HIV. Concerning HIV transmission modes knowledge, 22% of MSM answered correctly in the 5 questions, according to UNGASS guidance. In the univariate analysis, cocaine use, education level and type of sexual partner were independently associated with the unprotected anal intercourse.Conclusion The prevalence of HIV infection in MSM in Cyprus remains stable at low levels similar to other Central European countries. The high response rate indicates the broad acceptance of such studies. Knowledge awareness campaigns should be implemented regarding the transmission modes and risky sexual behaviours as well as interventions for the promotion of HIV testing.
Keywords: HIV prevalence; Men; Sex; Sexual behaviours